Task: "\\frac{dy}{dx} = 1 + (\\frac{dy}{dx})^2" .
Solution: It is convinient to use new variable: "f = \\frac{dy}{dx}" (1).
By substitution (1) it is possible to transform initial equation in the following form:
"f^2 -f + 1 = 0"
This is an ordinary quadratic equations with the following solution:
"D = (-1)^2 - 4 \\cdot 1 \\cdot 1 = -3 \\\\\nf_{1,2} = \\frac{1 \\pm \\sqrt{D}}{2} = \\frac{1 \\pm \\sqrt{3}i}{2} \\\\\nf_1 = \\frac{1}{2} + \\frac{\\sqrt{3}}{2}i,\\ f_2 = \\frac{1}{2} - \\frac{\\sqrt{3}}{2}i"
where "i^2 = -1" — imaginary unit.
By using reversed transform of (1) we can get the solutions:
"y_{1,2} = \\int f_{1, 2} dx"
To integrate complex functions it is possible to use the feature of continous contour integrals:
"\\int (u(x) + iv(x))dx = \\int u(x) dx + i\\int v(x)dx"
Thus, the solutions are:
"y_1(x) = \\int f_1 dx = \\int (\\frac{1}{2} + \\frac{\\sqrt{3}}{2}i)dx = \\int \\frac{1}{2}dx + i\\int \\frac{\\sqrt{3}}{2}dx=(\\frac{1}{2} + \\frac{\\sqrt{3}}{2}i)x + C_1 \\\\\ny_2(x) = \\int f_2 dx = \\int (\\frac{1}{2} - \\frac{\\sqrt{3}}{2}i)dx = \\int \\frac{1}{2}dx - i\\int \\frac{\\sqrt{3}}{2}dx=(\\frac{1}{2} - \\frac{\\sqrt{3}}{2}i)x + C_2"
So, the final solution is:
"y(x) = (\\frac{1}{2} \\pm \\frac{\\sqrt{3}}{2}i)x + C"
Answer: "y(x) = (\\frac{1}{2} \\pm \\frac{\\sqrt{3}}{2}i)x + C"
Comments
Leave a comment